The goode guide to wine : a manifesto of sorts - Goode, Jamie (University of California Press, 2020)
"Who will have the last word on wine, if not Jamie Goode? Over the last decade, Goode has embarked on almost nonstop travel through the world's vineyards in an effort to understand the beautifully diverse and complicated world of wine. His hard-nosed pursuit of the most interesting stories to tell about wine has led us here, to The Goode Guide to Wine. This book--a sort of manifesto--distills many of the observations, lessons, and opinions that have made Jamie Goode a renowned voice within the wine world. In a series of short, pithy, and often rather blunt chapters, he celebrates what is exciting and interesting about wine, asks how we could do things better, and points out some of the absurdities of wine culture. Jamie Goode has a distinct philosophy when it comes to wine, and he knows you may disagree; if you do, that means it's working. The Goode Guide to Wine is a book designed to provoke and inspire in equal measure, encouraging the reader to be critical and to see the world of wine through fresh eyes"--